Study of the Effect of Various Human Activities on the Distribution of some Organophosphorus Pesticides in the Marine Waters of the Coast of Lattakia ity - حسام الدين كريم لايقه (Latakia University Journal -Basic Sciences Series, 2023)
This research focused on the determination of the concentrations of some organophosphorus pesticides in five different areas of the coast of Latakia city (northern estuary of Nahr al-Kabir, Al-Marfa, Afamia, Sports City and Sakiet Moussa) using gas chromatography technology related to spectrometry gaschromatography/MS (GC/MS). The results showed that the total concentrations of organophosphorus pesticides were significantly higher in the marine waters of the port site (111.115μg/l) and the northern mouth of the Kabir River (39.899μg/l), with the lowest values recorded at the Sports City site (1.158μg/l). Diazinon recorded the highest values in the harbor area (71.802μg/l), and Dimethoat in the northern estuary of the Kabir (26.592μg/l). It was noted that the Sports City area is the least studied area of concentrations of these pollutants compared to various other studied sites, while the diversity is great in the number of vehicles.